The Potential of Secondary Metabolites in Medicinal Plants as Anti–Quorum Sensing in Biofilms: A Comprehensive Review - Salsabila Aqila Putri; Euis Julaeha; Natsuko Kagawa; Dikdik Kurnia (Journal of Chemistry)
The formation of biofilms occurs due to a group of bacteria gathering together. The increasing of cell density will stimulate chemical signals for bacteria to communicate through quorum sensing system. Quorum sensing plays a role for competition, virulence, resistance, and pathogenesis. Quorum sensing produces signaling response called as autoinducers. Gram-negative bacteria produce N-acyl-L-homoserine lactones as autoinducer, while quorum sensing in Gram-positive bacteria produces autoinducing peptides. By looking at quorum sensing responses in bacterial pathogenesis and resistance, the study of natural antibiotic agents became a particular concern for researchers. This review summarizes the study of quorum sensing systems acting on Gram-positive and Gram-negative bacteria, the role of quorum sensing on biofilm formation by pathogenic bacteria, and the potential use of medicinal plants as natural anti–quorum sensing agents reviewed in vitro and in silico. The use of extracts from leaves, fruits, flowers, stems, and isolated compounds of some types of plants and essential oils has been successfully tested to have anti–quorum sensing activity.